Why Uzbekistan plays a significant role in Central Asia (US perspective)? - Bobur Bakhrom ugli Toshbekov (International Journal of Economics, Business and Innovation Research, 2022)
When Uzbekistan left the Soviet Union 30 years ago and declared independence, the United States was one of the first to recognize it and establish diplomatic relations. Former US ambassadors were given the floor at a virtual forum hosted by the Republican Embassy in Washington. According to Uzbek Ambassador to the United States and Canada Javlon Vahabov, they have made an invaluable contribution to making the two countries, strategic partners. In 1992, the American Embassy was opened in Tashkent. Henry Clark, the first US ambassador to Uzbekistan, recalls how the country spent its days of coupons and economic hardship when it was difficult to boil a pot. Political scientist Ainura Akmatalieva mentions “In the US Central Asian policy, the desire to strengthen relations with Kazakhstan and Uzbekistan will prevail over regional dialogue”. It is stated that the USA focuses on Uzbekistan because of Afghanistan, and stability. In this paper, I will analyze why the relationship between Uzbekistan and USA is stronger than in other Central Asian countries, and supporting with a literature review based on open sources (articles, reports, news), accompanied with applying International Relations theory, and in the last part, I can try to conclude by recommending policy to The President of the Republic of Uzbekistan, Shavkat Mirziyoyev